Food security dynamics in emerging regions: Integrating dietary diversity and expenditure-based measures - Shabilla Uswatun Hasanah (Jurnal Inovasi Pangan dan Gizi, 2026)
Background: Intan Jaya Regency and Puncak Regency in Central Papua Province are among the five regencies with the lowest food security index in Indonesia. As a newly established province, ensuring adequate food security constitutes a strategic foundation for sustainable regional development. This study aims to analyze the level of food security, the degree of food diversification, and the socioeconomic factors influencing household food security in Central Papua Province. Methods: The research utilizes secondary data from the March 2024 SUSENAS (Survei Sosial Ekonomi Nasional/National Socio-Economic Survey), published by Badan Pusat Statistik (Central Bureau of Statistics), comprising a total sample of 1,060 households across Intan Jaya and Puncak Regencies. Food security analysis is conducted using the Johnsson and Toole method, which combines indicators of food expenditure share and energy adequacy levels, while the factors affecting food security are identified through binary logistic regression. Findings: The results indicate that (1) household food security in Central Papua Province falls into the food-insecure category, (2) the level of food diversification is categorized as high, and (3) significant socioeconomic determinants include household income, household size, and the education level of the household head. The integration of the Johnsson and Toole method with food diversification analysis within the context of a newly formed province enables this study to provide a more detailed and comprehensive depiction of food security dynamics in Central Papua Province. Conclusion: Household food security in Central Papua Province remains food-insecure despite diversified diets, with income, family size, and education as key determinants, underscoring the need for income support, agricultural training, and improved educational access. Novelty/Originality of this article: This study uniquely integrates the Johnsson and Toole method with dietary diversification analysis using 2024 SUSENAS data from Badan Pusat Statistik to uncover the paradox of high diet diversity yet persistent food insecurity in Intan Jaya Regency and Puncak Regency.